Isolation and Extraction of Medicinally Important Oil from the Seeds of Melia composita Willd - Indrayan, A.K.; Priya, Ms. (Asian Journal of Chemistry, 2010)
The extracted material from the dried seeds of Meliacomposita is used as an indigenous medicine. Using the varioussolvents for extraction, viz., diethyl ether, petroleum ether, benzene,n-hexane, methanol and ethanol, the materials of varied compositionare obtained in varied yields, expected to have varied medicinalvalue.